LEARNING STRATEGIES USED BY THE STUDENTS OF ENGLISH DEPARTEMENT OF STAIN PALOPO - Said Ruqiyyat Yuyun (Institut Agama Islam Negeri Palopo, 2018)
This research aimed at finding out the learning strategy used by sixth semester students of English Department of STAIN Palopo This research applied quantitative method, the data were collected from questionnaire of SILL (Strategies Inventory of Language Learning) developed by Oxford; there are six types of learning strategies, they are memory, cognitive, compensation, metacognitive, affective and social strategies. The researcher used Strategy Inventory for Language Learning (SILL) version 7.0 as instrument to collect the data in this research. Questionnaire was used to get quantitative data about learning strategies of the students.. The result of the study shows that the most frequently used learning strategy by students is meta cognitive; this strategy is also the highest level of usage. These strategies help students to coordinate their learning and plan language leaning in efficient way. Metacognitive strategies (e.g., identifying ones own learning style preferences and needs, planning for an target language task, gathering and organizing materials, arranging a study source and a schedule, monitoring mistakes, and evaluating task success, and evaluating the success of any type of learning strategy) are employed for managing the learning process overall.